Answer:
x = 0
Step-by-step explanation:
![2(\sqrt{x}+3)=6](https://tex.z-dn.net/?f=2%28%5Csqrt%7Bx%7D%2B3%29%3D6)
Expanding the left hand side we get
![\Rightarrow 2\sqrt{x}+6=6](https://tex.z-dn.net/?f=%5CRightarrow%202%5Csqrt%7Bx%7D%2B6%3D6)
Taking 6 from left hand side to right hand side
![\Rightarrow 2\sqrt{x}=6-6\\\Rightarrow 2\sqrt{x}=0](https://tex.z-dn.net/?f=%5CRightarrow%202%5Csqrt%7Bx%7D%3D6-6%5C%5C%5CRightarrow%202%5Csqrt%7Bx%7D%3D0)
Dividing both sides by 2
![\Rightarrow \sqrt{x}=\frac{0}{2}\\\Rightarrow \sqrt{x}=0\\\Rightarrow x=0](https://tex.z-dn.net/?f=%5CRightarrow%20%5Csqrt%7Bx%7D%3D%5Cfrac%7B0%7D%7B2%7D%5C%5C%5CRightarrow%20%5Csqrt%7Bx%7D%3D0%5C%5C%5CRightarrow%20x%3D0)
So, x = 0
Answer:
u= 2.5
Step-by-step explanation:
Using BIDMAS
Step 1: Expand the bracket
9(u-2) + 1.5u=8.25
9u-18+1.5u=8.25
Step 2: collect like terms
9u+1.5u=8.25+18
10.5u=26.25
Step 3: Divide both sides by 10.5 to get u
u=
= 2.5
Multiply the denominator by 4
Answer:
sin 2x + cos x = 2 sin x cos x + cos x = (2 sin x + 1)cos x
Step-by-step explanation:
Given the expression: sin 2x + cos x,
then we can use the formula: sin 2x = 2 sin x cos x, which gives:
sin 2x + cos x = 2 sin x cos x + cos x = (2 sin x + 1)cos x
So there you have two expressions in terms of sin x and cos x, as requested. :D